Optimization of Extraction Conditions to Enhance Polyphenol Content and Antioxidant Activity İn Orthosiphon Aristatus Leaves - Febriyanto, Dimas; Setyawati, Inda; Ambarsari, Laksmi; Nurcholis, Waras (Molekul, 2026)
ABSTRACT. Orthosiphon aristatus (Java tea) is a medicinal plant known for its high polyphenol content and antioxidant properties. Unlike previous studies that focused solely on solvent type or temperature, this study simultaneously optimizes temperature and pH extraction parameters to achieve maximal bioactive compound recovery. This study aimed to optimize extraction parameters—temperature and pH—to enhance polyphenol yield and antioxidant activity in methanolic extracts of Java tea leaves. Samples were extracted at temperatures ranging from 30 °C to 80 °C (pH 7) and pH levels from 2 to 6 (at room temperature). Total phenolic content (TPC) and total flavonoid content (TFC) were determined to quantify polyphenol levels, and antioxidant activity was evaluated using four complementary in vitro assays: DPPH, ABTS, FRAP, and CUPRAC. The highest TPC (9.68 mg GAE/g DW) and TFC (6.53 mg QE/g DW) were observed at 70 °C and 80 °C, respectively. Maximum antioxidant activities were observed at 70–80 °C and pH 2–3, with peak values of 102.71 µmol TE/g DW (ABTS), 101.9 µmol TE/g DW (FRAP), and 56.12 µmol TE/g DW (CUPRAC). A strong correlation was found between phenolic content and antioxidant capacity. These findings highlight the critical role of extraction conditions in maximizing the biofunctional potential of O. aristatus and support its application in pharmaceutical and nutraceutical formulations. The study provides a scientific basis for developing standardized extraction protocols to improve functional ingredient consistency in herbal product development. Keywords: Antioxidant activity, extraction optimization, Orthosiphon aristatus, pH effect, temperature